Quintessence of Dust: The Science of Matter and the Philosophy of Mind - Redner, Harry, (Value Inquiry Book Series;, 2020)
Quintessence of Dust by Harry Redner argues for a science of matter and a philosophy of mind based on emergence. Mind emerges from matter through five essential stages - "quintessence" ( Hamlet ). Human mind is differentiated from animal mind primarily by reference to art ( Homo ludens ). This approach draws support from Donald, Edelman and other palaeoanthropologists, psychologists and neurologists. The emergent relation between two entities is defined as an indissoluble non-identity. The "mind as machine" thesis, artificial intelligence and cognitivism are criticised. The alternative emergentist approach comes close to Spinoza. The book attempts a synthesis of the natural sciences, social sciences and humanities based on philosophic premises.